Perancangan Perabot Multifungsi untuk Ruang Huni Terbatas - Burhan Leonardi Poetra (Intra, 2016)
The high need of urban community for living space causes the lack of spaces available offered by big cities, and because of that people starts to build vertical living spaces. The problem is, some size of the rooms available doesn’t fit the need for some people to do their activities. This project is intended to help the need of some people who live in a narrow living space such as a small apartment, small dormitory, flat, and other narrow living space for doing their activities which relates to the function of the furniture designed. Observing the need of the people is the first method to begin with, then gathering the information needed, brainstorm and gathering the idea to get the concept that make the design’s boundaries, then making a real scale, so that, the model made can be tested to optimize then. At the end some of the function offered by this multifunction furniture are sleeping facilities, working facilities, storage facilities that oriented in the eficiency, efectivity, and form that follow its function.